The Relation between Qur’an and Philosophy: A descriptive comparative study - “Muhammad Nabil” Tahir al-Omari - العمري, "محمد نبيل" طاهر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2018)
This study discusses one of the contemporary issues, namely the reconciliation between Qur’an and Philosophy in terms of principles, objectives and results, and presents the views of the supporters and opponents of the reconciliation idea. The study presents the relation between the two terms: wisdom and philosophy, the extent to which the two terms are identical, scholars’ views on this issue and its impact on Islamic Studies. Finally, the study presents a set of decisive conclusions.